VASYL STEFANYK’S CREATIVE PERSONALITY IN THE RECEPTION OF PRECARPATHIAN SCHOLARS - Ushnevych, S. E. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article conceptualizes the creative personality of Vasyl Stefanyk through the prism of literary and artistic reading of Precarpathian scholars resparches in the problems of artistic reception and interpretation of the new typological model of the novel about the artist.